When The Jobs of The Future Meet Their Key Competencies: An Exploratory Study to Align the Perspective of World Economic Forum And the Occupations in ESCO Database - Marlene AMORIM; Carolina PAN; Barbara CARVALHO; Mario RODRIGUES; Gabriel SILVA; Marta FERREIRA DIAS (Communications of International Proceedings, 2022)
In recent years there has been a multiplication of studies and policy documents that put forward priorities for the reskilling of professionals to meet the demands of the future of work. The technological evolution and digital transformation that is being experienced across industries is motivating a paradigm shift in the occupations and in the nature of work. New skills are being valued for the labor market and new professions are emerging. According to the World Economic Forum (WEF) there are 20 professional clusters that will stand out in the near future, and will experience increasing demand across industries. Likewise, other functions and occupations have been highlighted as those that will be losing ground in the job market. This raises concerns about the ability of companies and economies to meet, in due time, the needs for the development of new skills and paths for professional education and training, as well as for the deployment of requalification programs for those that occupy the jobs that are disappearing. The effectiveness of this debate, and the ability of reaching timely discussions, policy proposals and concrete training programs often falls behind the desired pace due to the immense proliferation of reports, lists and multiple designations for competencies, skills and future occupations and professions. This study offers a contribution for advancing in the consistency in the terminology and the designations adopted  for the jobs and competences of the future by bringing together the list of jobs of the future proposed by the WEF, and the classification of occupations and associated skills developed in ESCO, the European Skills, Competences Qualifications and Occupations database, to investigate if there is a shortlist of competencies that are transversal to the jobs of the future. The study results supported that there is a number of competences that are predominately present across different jobs of the future, therefore pointing towards the need to develop education and training programs that cover such range of elementary job market attributes that will be valuable to many professionals across different fields. Moreover, the study also illustrates the urgency in the need to advance in the standardization in the discourse about competencies and skills development, across entities, policy makers, taxonomies and related classification tools, to allow for a quicker advances in the development of data analysis tools addressing job market and training data.
Keywords: WEF; ESCO; skills; demand; competencies; labor market; future